2021
DOI: 10.3389/fimmu.2021.756495
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Vγ9Vδ2 T-Cell Therapy Promotes Pulmonary Lesion Repair: An Open-Label, Single-Arm Pilot Study in Patients With Multidrug-Resistant Tuberculosis

Abstract: The WHO’s “Global tuberculosis report 2020” lists tuberculosis (TB) as one of the leading causes of death globally. Existing anti-TB therapy strategies are far from adequate to meet the End TB Strategy goals set for 2035. Therefore, novel anti-TB therapy protocols are urgently needed. Here, we proposed an allogeneic Vγ9Vδ2 T-cell-based immunotherapy strategy and clinically evaluated its safety and efficacy in patients with multidrug-resistant TB (MDR-TB). Eight patients with MDR-TB were recruited in this open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Treating this impairment is theoretically feasible, but progress has been slow [33]. It is only recently that some achievements in immunotherapy based on γ-δT cells have emerged [34][35][36]. Prior to this, Yuan, Fawei, and colleagues [37] proposed a different viewpoint, suggesting that γ-δ1T cells play an immune suppressive role in sepsis.…”
Section: Gamma-delta T Cells (γ-δT Cells)mentioning
confidence: 99%
“…Treating this impairment is theoretically feasible, but progress has been slow [33]. It is only recently that some achievements in immunotherapy based on γ-δT cells have emerged [34][35][36]. Prior to this, Yuan, Fawei, and colleagues [37] proposed a different viewpoint, suggesting that γ-δ1T cells play an immune suppressive role in sepsis.…”
Section: Gamma-delta T Cells (γ-δT Cells)mentioning
confidence: 99%
“…Studies from our group demonstrated the safety and efficacy of allogeneic Vδ2 T cells derived from healthy donors in the treatment of late-stage lung and liver cancer patients, 11,12 pointing towards the potential of off-the-shelf Vδ2 T cell products in cancer immunotherapy. Furthermore, the successful application of γδ T cells in treating MDR-TB 13 and their functional attenuation in COVID-19 patients [87][88][89] expanded our understanding of their therapeutic potential in combating challenging infectious diseases. Strikingly, the regulatory role of γδ T cells in the social behavior of mice 90 and the achievement of 100% complete remission in leukemia patients (NCT03533816) who received γδ T cell therapy have heightened our anticipation regarding the physiological functions of γδ T cells.…”
Section: Chronological Milestones Of γδ T Cell Researchmentioning
confidence: 99%
“…[5][6][7][8][9][10] Since 2016, we have been at the forefront of translating the application of allogeneic γδ T cells, specifically the Vγ9Vδ2 + γδ T subset, from the laboratory to clinical practice, with the aim of renormalizing the dysfunctional immune system in patients with advanced solid tumor 11,12 or multidrug-resistant tuberculosis (MDR-TB). 13 In a comprehensive study involving 132 patients diagnosed with various types of cancer (including liver, lung, pancreatic, breast, and others), we administered a total of 414 cell infusions. Through this investigation, we not only established the safety of transferring allogeneic Vγ9Vδ2 + γδ T cells (abbreviated as Vδ2 T cells below) generated from healthy donors' PBMCs after in vitro expansion but also demonstrated their clinical efficacy in extending patient survival and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The most feasible candidate are chronic infections, such as tuberculosis (Tbc). Feasible strategies in this regard would include engineered T cells displaying TCRαβ recognizing Tbc-specific pMHC-I or -II complexes expressed by infected cells, as well as unmodified Tγδ cells targeting nonpeptidic Tbc antigens [39,40].…”
Section: Bacterial Infectionsmentioning
confidence: 99%